An Uncommon Osseous Frontal Sinus Tumor: Monostotic Paget's Disease. (7th December 2013) - Labajian, Varant; Landry, Evie; Alfawwaz, Fahad; Lai, Chi; Kilty, Shaun J.
Abstract : Paget's disease of the bone is a disorder characterized by abnormal breakdown and formation of bone tissue. The cause is believed to be either viral or genetic in origin. Most of the time, patients are asymptomatic. Diagnosis is supported by findings from multiple modalities including serum markers, imaging, bone scans, and histology. We present a rare case of Paget's disease of the bone involving the frontal sinus. We review the relevant clinical, diagnostic, and histological findings. We also suggest indications for the management of monostotic Paget's disease of the frontal sinus.